Review: The Old Testament in the New Testament. Essays in Honour of J. L. North - Hays, R. (The journal of theological studies, 2004)
The Old Testament in the New Testament. Essays in Honour of J. L. North. Steve Moyise Pp. 302 (Journal for the Study of the New Testament, Supplement Series, 189.) Sheffield Academic Press 2000 1 84127 061 x. £ 49/$82